Application of Fin System on Adsorption of Methylene Blue Dye using Adsorbent Coating Layer: Mathematical Formulae - Abd Hamid, Shazlina; Ismail, Suzylawati (ITB Journal Publisher, LPPM ITB, 2017)
Treatment of dye solution using fin system is one of the new adsorption application techniques that can replace expensive conventional adsorption treatment units that mostly used in industries. The fins will work as the media of adsorbent coating and immerse in a tank containing dye wastewater. The purpose of present study is to develop simple mathematical equations for the finâs system by using adsorbent coating layer (ACL) as an adsorbent. By installing coated fins inside the tank, the concentration of dye can be easily reduced up to 90 %. The equilibrium adsorption data was best met by the Langmuir isotherm, indicating the adsorption is homogeneous surface and in monolayer state.Â The mathematical formula developed from the isotherm model of adsorption was revealed to be used in large scale application for the removal of methylene blue dye from industrial wastewater since the percent error between calculated and experimental values were less than 15%.